The Impact of Loneliness to Problematic Smartphone Use with Self Perception as a Mediator (Universitas Negeri Semarang, 2019)
The purpose of this research was to identify and analyze the impact of Loneliness with the mediator of Self Perception to Problematic Smartphone Use of students. The population in this research were all State High Schools in Semarang with a sample of 320 students selected by using cluster random sampling technique. Data collection using R-UCLA Loneliness Scale version 3, Smartphone Addiction Scale Short Version and Adolescents Self-perception Short Scale. Data analysis using bootstrapping bias-corrected. The results of the statistical data showed that loneliness is positively predicted by the PSU with self-perception. Therefore, the higher the level of loneliness through low self-perception of students, the higher the PSU. This research provided counselors with an understanding of the excessive use of smartphones in students considering that there are currently many students who experience personal and social problems in their daily lives due to smartphone use.